The Effect Of Training And Leadership On The Performance Of PT Gyata Anugerah Persada Employees - Andi; Muhammad Fauzan Azhmy; Fajar Pasaribu (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
The purpose of this study was to determine and analyze the effect of training and leadership on employee performance at PT. Gyatha Anugerah Persada Medan. The data used are primary data and secondary data. Primary data was collected through questionnaires distributed to employees, while secondary data was obtained from documentation studies obtained from various information held by the company and the results of previous research. The data analysis method uses quantitative methods, namely Multiple Linear Regression analysis. The population in this study were all employees of PT. Gyatha Anugerah Persada Medan and the sample in this study was the total population of 113 employees. The results showed that training (X1) and leadership (X2) on employee performance, it was concluded that there was a positive and significant effect of training and leadership on employee performance at PT. Gyatha Anugerah. While the ability of Training (X1) and Leadership (X2) together can explain changes in Employee Performance (Y) by 41.5% while the remaining 58.5% is influenced by other factors not discussed in this study.